2022
DOI: 10.1029/2021jb023321
|View full text |Cite
|
Sign up to set email alerts
|

Critical Zone Structure by Elastic Full Waveform Inversion of Seismic Refractions in a Sandstone Catchment, Central Pennsylvania, USA

Abstract: Seismic imaging provides key information for revealing structures within Earth's critical zone (CZ) and quantifying subsurface fluid properties. The P‐wave velocity (Vp) models estimated by seismic refraction tomography or acoustic full waveform inversion (FWI) are useful to delineate the thicknesses of weathered bedrock but ambiguously map fluid properties in CZ. Considering the complementary sensitivity of S‐wave to subsurface fluid saturation, we explore advanced elastic full waveform inversion (EFWI) to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 50 publications
(96 reference statements)
0
25
0
Order By: Relevance
“…To avoid the challenge of matching exact amplitudes varied with shots and traces/offsets, we solve the correlative‐based misfit that measures the global phase closeness between dm ${d}_{m}$ and dobs ${d}_{obs}$ as follows: f()boldvp=()1dm()xr,t;xsdobs()xr,t;xsdtdm2()xr,t;xsdtdobs2()xr,t;xsdtdxrdxs, $f\left({\mathbf{v}}_{p}\right)=\int \int \left(1-\frac{\int {d}_{m}\left({\mathbf{x}}_{r},t;{\mathbf{x}}_{s}\right){d}_{obs}\left({\mathbf{x}}_{r},t;{\mathbf{x}}_{s}\right)dt}{\sqrt{\int {d}_{m}^{2}\left({\mathbf{x}}_{r},t;{\mathbf{x}}_{s}\right)dt}\sqrt{\int {d}_{obs}^{2}\left({\mathbf{x}}_{r},t;{\mathbf{x}}_{s}\right)dt}}\right)d{\mathbf{x}}_{r}d{\mathbf{x}}_{\boldsymbol{s}},$ where t , xr ${\mathbf{x}}_{\boldsymbol{r}}$, and xs ${\mathbf{x}}_{\boldsymbol{s}}$ represent the time, receiver, and source coordinates, respectively. The correlative misfit can relax the requirement for offset‐ and shot‐dependent amplitude fitting and enables FWI to be robust; this approach has been applied to several field data studies (e.g., Liu et al., 2022).…”
Section: Methodology Of Correlative Double‐difference Time‐lapse Fwi ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the challenge of matching exact amplitudes varied with shots and traces/offsets, we solve the correlative‐based misfit that measures the global phase closeness between dm ${d}_{m}$ and dobs ${d}_{obs}$ as follows: f()boldvp=()1dm()xr,t;xsdobs()xr,t;xsdtdm2()xr,t;xsdtdobs2()xr,t;xsdtdxrdxs, $f\left({\mathbf{v}}_{p}\right)=\int \int \left(1-\frac{\int {d}_{m}\left({\mathbf{x}}_{r},t;{\mathbf{x}}_{s}\right){d}_{obs}\left({\mathbf{x}}_{r},t;{\mathbf{x}}_{s}\right)dt}{\sqrt{\int {d}_{m}^{2}\left({\mathbf{x}}_{r},t;{\mathbf{x}}_{s}\right)dt}\sqrt{\int {d}_{obs}^{2}\left({\mathbf{x}}_{r},t;{\mathbf{x}}_{s}\right)dt}}\right)d{\mathbf{x}}_{r}d{\mathbf{x}}_{\boldsymbol{s}},$ where t , xr ${\mathbf{x}}_{\boldsymbol{r}}$, and xs ${\mathbf{x}}_{\boldsymbol{s}}$ represent the time, receiver, and source coordinates, respectively. The correlative misfit can relax the requirement for offset‐ and shot‐dependent amplitude fitting and enables FWI to be robust; this approach has been applied to several field data studies (e.g., Liu et al., 2022).…”
Section: Methodology Of Correlative Double‐difference Time‐lapse Fwi ...mentioning
confidence: 99%
“…To avoid the challenge of matching exact amplitudes varied with shots and traces/ offsets, we solve the correlative-based misfit that measures the global phase closeness between 𝐴𝐴 𝐴𝐴𝑚𝑚 and 𝐴𝐴 𝐴𝐴𝑜𝑜𝑜𝑜𝑜𝑜 as follows: where t, 𝐴𝐴 𝐱𝐱𝒓𝒓 , and 𝐴𝐴 𝐱𝐱𝒔𝒔 represent the time, receiver, and source coordinates, respectively. The correlative misfit can relax the requirement for offset-and shot-dependent amplitude fitting and enables FWI to be robust; this approach has been applied to several field data studies (e.g., Liu et al, 2022).…”
Section: Methodology Of Correlative Double-difference Time-lapse Fwi ...mentioning
confidence: 99%
“…X. Liu et al (2022) used the NC norm to apply FWT in the CZ despite working with relatively noisy data, while Borisov et al (2020) found that using the NC norm helped contend with unmodeled anelastic and 3D effects. In choosing the NC norm, the corresponding adjoint source for each shot at Earth and Space Science 10.1029/2023EA003248 each receiver location is given by f † i,j = ûi,j ∫ T ûi,j • û0 i,j dt) -û0 i,j (Choi & Alkhalifah, 2012), where i and j are the shot and receiver indices respectively.…”
Section: Full-waveform Tomography Workflowmentioning
confidence: 99%
“…To date, however, FWT has only been used to study the near surface on a handful of occasions (e.g., Cai & Zelt, 2022;J. Chen et al, 2017;Köhn et al, 2018;X. Liu et al, 2022;Sheng et al, 2006;W.…”
Section: Introductionmentioning
confidence: 99%
“…Other observations report a larger‐than‐expected range, including high V p /V s values greater than 4 (Flinchum et al., 2020; Pasquet et al., 2015a; Stümpel et al., 1984) or even as high as 20 (Salas‐Romero et al., 2021). There are reports of V p /V s values less than 1.4 in the CZ of Brazil (Trichandi et al., 2022), in dry soils (Salem, 2015), and in full waveform inversion results in the CZ of Pennsylvania (Liu et al., 2022). These observations raise an important question: what can anomalous V p /V s values tell us about physical and chemical processes that drive CZ evolution?…”
Section: Introductionmentioning
confidence: 99%